Effect of selected prebiotics on the growth of lactic acid bacteria and physicochemical properties of yoghurts. (February 2019) - Delgado-Fernández, Paloma; Corzo, Nieves; Olano, Agustín; Hernández-Hernández, Oswaldo; Moreno, F. Javier
Abstract: The feasibility of manufacturing yoghurts with three prebiotics, i.e., fructooligosaccharides (FOS), galactooligosaccharides (GOS) or lactulose added at two concentrations (2 and 4%, w/v) was investigated. Physicochemical and microbial characterisation was conducted on the effect of prebiotics on acidification, viability of Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus, lactose and prebiotic consumption and production of organic acids during fermentation (up to 6 h) and cold storage (for 28 d). GOS and FOS remained unaltered throughout fermentation and cold storage, while the viability of starter culture was similar to that observed in the control yoghurt. Yoghurts manufactured with 4% lactulose showed a significant decrease of lactulose content associated with a lower decrease of lactose relative to the control. This effect was associated with a significant increase (2.2 log10  cfu mL −1 ) in L . delbrueckii ssp. bulgaricus and a moderate decrease (1.0 log10  cfu mL −1 ) in S . thermophilus at the end of cold storage.